Management patients information based finger print - Ahmed Bashar Fakhri; Huda Farooq Jameel; Mustafa Falah Mahmood (Institute of Advanced Engineering and Science, 2022)
The fingerprint is certainly one of the distinguishing features of the human body that is easily available and identifies one individual from another. The fingerprint sensor increases this distinctiveness, which is a device that can automatically classify or identify a person. The fingerprint based medical system is a more efficient means of storing clinical data for patients. It makes take advantage of fingerprint recognition technology to quickly and easily for determine the patient's past medical history. The system consists of an Arduino UNO board, a fingerprint sensor, an secure digital (SD) card module, and a micro-SD card. The suggested technology allows the use of a micro-SD card to store patient information as well as send it by internet. When this system was compared to the manual technique, the results indicate that the main advantage is that the proposed device saves a significant amount of time that manual searching and enrolling requires. Patients' information is simply collected and managed with this system, which has enhanced dependability, durability, and efficiency. It provides improved speed and performance, as well as better data security because the data is stored within the device.